2007
DOI: 10.1242/jcs.003012
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism controls the Ca2+ oscillations triggered by activation of ascidian eggs and has an absolute requirement for Cdk1 activity

Abstract: Fertilisation in ascidians triggers a series of periodic rises in cytosolic Ca2+ that are essential for release from metaphase I arrest and progression through meiosis II. These sperm-triggered Ca2+ oscillations are switched off at exit from meiosis II. Ascidian zygotes provided the first demonstration of the positive feedback loop whereby elevated Cdk1 activity maintained these Ca2+ oscillations. Since then it has been reported that Cdk1 sensitises the type I inositol trisphosphate [Ins(1,4,5)P3] receptor in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
(53 reference statements)
2
9
0
Order By: Relevance
“…In another ascidian, A. aspersa, DN-cyclin B steadily activates Cdk1 and prolongs the sperm-induced [Ca 2 þ ] i oscillations (Levasseur and McDougall, 2000). Furthermore, it has been shown that Cdk1 activity is both necessary and sufficient for phase II [Ca 2 þ ] i oscillations (Levasseur et al, 2007). In the present study, GST-D85N-cyclin B also maintained ERK activity and prolonged the period of [Ca 2 þ ] i oscillations in the Phallusia eggs; the period of [Ca 2 þ ] i oscillations correlated with both ERK and Cdk1 activities.…”
Section: Effect Of Cdk1 On [Ca 2 þ ] I Oscillationssupporting
confidence: 69%
“…In another ascidian, A. aspersa, DN-cyclin B steadily activates Cdk1 and prolongs the sperm-induced [Ca 2 þ ] i oscillations (Levasseur and McDougall, 2000). Furthermore, it has been shown that Cdk1 activity is both necessary and sufficient for phase II [Ca 2 þ ] i oscillations (Levasseur et al, 2007). In the present study, GST-D85N-cyclin B also maintained ERK activity and prolonged the period of [Ca 2 þ ] i oscillations in the Phallusia eggs; the period of [Ca 2 þ ] i oscillations correlated with both ERK and Cdk1 activities.…”
Section: Effect Of Cdk1 On [Ca 2 þ ] I Oscillationssupporting
confidence: 69%
“…In C. intestinalis, we firstly demonstrated that MPF kinase activity is significantly high in metaphase-I blocked oocytes and decreases after fertilization and sperm-triggered calcium oscillation (Russo et al, 1996). Other authors confirmed and extended our initial observation (McDougall and Levasseur, 1998;Levasseur and McDougall, 2000;Levasseur et al, 2007). This can be considered an initial and circumstantial evidence on the existence of a CSF activity able to stabilize MPF complex.…”
Section: Presence Of a Csf-like Activity In C Intestinalissupporting
confidence: 82%
“…In analyses of Ca 2+ signals and cell‐cycle kinases during ascidian fertilization, MPF has been shown to upregulate Ca 2+ ‐wave production, given that oscillations occur when MPF activity is normally elevated or artificially raised; conversely, oscillations are blocked when MPF is either naturally deactivated (between meiotic divisions and at the end of meiosis) or experimentally downregulated by MPF inhibitors (Levasseur and McDougall, ; Levasseur et al, ; Sensui et al, ). Based on several lines of evidence, MPF‐mediated stimulation of Ca 2+ signals involves the modulation of IP 3 levels rather than alteration in IP 3 R sensitivity to IP 3 (Levasseur and McDougall, ; Levasseur et al, ).…”
Section: Comparative Biology Of Fertilization‐induced Calcium Signalsmentioning
confidence: 99%